A Rare Sequela of Acute Disseminated Encephalomyelitis. (26th May 2014) - Kodadhala, Vijay; Devulapalli, Saravana; Kurukumbi, Mohankumar; Jayam-Trouth, Annapurni
Abstract : Acute disseminated encephalomyelitis is a demyelinating disease, typically occurring in children following a febrile infection or a vaccination. Primary and secondary immune responses contribute to inflammation and subsequent demyelination, but the exact pathogenesis is still unknown. Diagnosis of acute disseminated encephalomyelitis is strongly suggested by temporal relationship between an infection or an immunization and the onset of neurological symptoms. Biopsy is definitive. In general, the disease is self-limiting and the prognostic outcome is favorable with anti-inflammatory and immunosuppressive agents. Locked-in syndrome describes patients who are awake and conscious but have no means of producing limb, speech, or facial movements. Locked-in syndrome is a rare complication of acute disseminated encephalomyelitis. We present a case of incomplete locked-in syndrome occurring in a 34-year-old male secondary to acute disseminated encephalomyelitis. Our case is unique, as acute disseminated encephalomyelitis occurred in a 34-year-old which was poorly responsive to immunosuppression resulting in severe disability.